Milk (2008) and The Times of Harvey Milk (1984): The Double Filmic Resurrection of the Mayor of Castro Street - Sara Villa (Altre Modernità, 2010)
On 18th November 1977, Milk recorded his will, "to be played only in the event of [his] death by assassination." In the first section of the tape, he declared his awareness of being the potential victim of such violence: "I fully realize that a person who stands for what I stand for, an activist, a gay activist, becomes the target or potential target for a person who is insecure, terrified, afraid, or very disturbed with themselves." Both Milk (2008), the most recent biopic dedicated to him, and The Times of Harvey Milk (1982), a previous Academy Award winning documentary, open on this testimony, and immediately follow it with the repertoire scenes of the day of his assassination. However, in spite of this initial mourning tonality, neither of these mainstream movies ends up being the martyrography of their main character, who was killed after receiving an escalating series of death threats. They rather proceed by relying on a journalistic style which resurrects Milk through his own words, which were constantly developed around the theme of hope. After the tragic first scene, both feature films reconstruct the keystones of Milk's political achievements by directly quoting from his frequent speeches, public and private writings and constant activism for the Gay Liberation Front.  The first out-of-the-closet gay man elected to a political office in the United States is therefore alive again on screen, in two radically different occasions. Firstly, through the documentary The Times of Harvey Milk, in a year when the anti-gay HIV backlash was leading to increasingly serious levels of homophobia throughout the country. Secondly, in a mainstream biopic of the years 2000, when the debate over gay marriage legislation is again dividing the United States of America. This paper aims at analyzing the ways in which this double filmic reappearance of Milk's political figure reactivates his piercing political activism in two different, but similarly crucial historical moments for the GLBT community, and contributes to the affirmation of an illuminated gay icon within the overall fight for human rights.